Universal capital endowment and wealth taxes could reduce wealth inequality - Stefan Bach (DIW Weekly Report, 2021)
Wealth is very unequally distributed in Germany. To effect a long-term reduction, the new Federal Government could focus on more effectively promoting home ownership, supplementary retirement provision, and other precautionary savings. However, a universal capital endowment could decrease wealth inequality much more rapidly and successfully. In this report, a universal capital endowment of up to 20,000 euros is simulated, which is granted to everyone 18 and older. These programs, which would require around 22.6 billion euros annually, could be financed by increasing the inheritance tax, implementing a recurrent wealth tax on the ultra wealthy, and taxing real estate properties more effectively. A universal capital endowment, which primarily increases the wealth of the lower and middle classes, paired with wealth taxes would significantly reduce wealth inequality in Germany: Simulations show that the Gini coefficient would decrease by five to seven percent as a result.
Keywords: H53; H24; D31; 330; Wealth formation; capital endowment (minimum inheritance); wealth taxation; wealth distribution